2018
DOI: 10.1186/s12913-018-3235-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke care after medical rehabilitation in Germany: a systematic literature review of the current provision of stroke patients

Abstract: BackgroundAlthough Germany’s acute care for stroke patients already has a good reputation, continuous follow-up care is still not widely available, a problem originating in the strict separation of inpatient and outpatient care. This gap in the German health care system does not just lead to patients’ potential readmission to inpatient care and compromise the sustainability of what they have accomplished during medical rehabilitation; it also places a burden on caregivers.MethodsTo illustrate the current proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
(38 reference statements)
0
18
0
3
Order By: Relevance
“…In the MAS-I study 24% of the caregivers reported moderate to high levels of stroke-related caregiver burden [11]. Several approaches have been suggested to close the gap between inpatient and outpatient care [52][53][54], however, social care has been understudied. An effective primary care-based stroke aftercare service must have a broad focus and must be based on an individual record of unmet needs including social needs [55].…”
Section: Discussionmentioning
confidence: 99%
“…In the MAS-I study 24% of the caregivers reported moderate to high levels of stroke-related caregiver burden [11]. Several approaches have been suggested to close the gap between inpatient and outpatient care [52][53][54], however, social care has been understudied. An effective primary care-based stroke aftercare service must have a broad focus and must be based on an individual record of unmet needs including social needs [55].…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been suggested to close the gap between inpatient and outpatient care [5254], however, social care has been understudied. An effective primary care-based stroke aftercare service must have a broad focus and must be based on an individual record of unmet needs including social needs [55].…”
Section: Discussionmentioning
confidence: 99%
“…Alter ( [31]. In Deutschland gibt es aktuell kein empfohlenes standardisiertes Vorgehen bei der Rehabilitation von Personen mit Schlaganfall, und die strikte Trennung von ambulanten und stationären Settings erschwert eine kontinuierliche Nachsorge [32]. Dadurch resultieren auch in der untersuchten Personengruppe Unterschiede hinsichtlich ihres bisherigen Zugangs zu rehabilitativen Maßnahmen, der nicht nur von der Zeit seit dem neurologischen Ereignis, sondern auch von anderen Faktoren wie Alter, sozioökonomischem Status und Komorbiditäten abhängen kann [33].…”
Section: Signifikanzunclassified